2015
DOI: 10.1097/jpa.0000000000000024
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Oral Health Curriculum by Physician Assistant Education Programs in 2014

Abstract: Efforts to equip PA faculty to teach oral health topics and clinical skills should continue as past efforts have resulted in wider integration of oral health subject matter into core PA curriculum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…According to Ferullo, Silk, and Savageau (2011), about 70% of MD degreegranting (n ¼ 72) and DO degree-granting (n ¼ 13) schools surveyed had fewer than 5 hours of oral health education. Langelier, Glicken, and Surdu (2015), the survey showed that 98 of the 125 respondents (78.4%) indicated that their "programs had integrated oral health content into their curriculum," which represented an increase from 2008 (p. 62).…”
Section: Preparing the Next Generation Of Women's Health Care Providersmentioning
confidence: 99%
“…According to Ferullo, Silk, and Savageau (2011), about 70% of MD degreegranting (n ¼ 72) and DO degree-granting (n ¼ 13) schools surveyed had fewer than 5 hours of oral health education. Langelier, Glicken, and Surdu (2015), the survey showed that 98 of the 125 respondents (78.4%) indicated that their "programs had integrated oral health content into their curriculum," which represented an increase from 2008 (p. 62).…”
Section: Preparing the Next Generation Of Women's Health Care Providersmentioning
confidence: 99%
“…Fluoride varnish was since added to the Bright Futures Periodicity Schedule in 2015 . Concomitantly, several major health organizations led oral health initiatives encouraging oral health awareness and education among their members, including the AAP Chapter Oral Health Advocate (COHA) program, American Academy of Physician Assistants Chapter Lecture Series on Oral Health , and nursing Oral Health Nursing Education and Practice (OHNEP) initiative. Nationally, practices are still transitioning to accommodate these relatively new requirements for fluoride varnish application for all children, especially with one in 10 commercially available Accountable Care Organizations including oral health as a benefit and one in four Medicaid contracts doing the same .…”
Section: Discussionmentioning
confidence: 99%
“…53 A 2013 survey of directors of PA education programs found that more than 70% of respondent programs had integrated oral health topics into the core content of their PA curricula. 54 However, whether training in oral health in PA education programs translates into screening and assessment of patients' oral health statuses in clinical practice remains unclear. A 2013 survey of PAs conducted by the American Association of Physician Assistants identified several key barriers to the effective integration of oral health competency into practice.…”
Section: Expanding the Oral Health Teammentioning
confidence: 99%